Religious Ritual as a Contestation Arena: The Experiences of Aluk Todolo Community in Tana Toraja of South Sulawesi - Idaman Idaman (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
This paper explores the extent to which Todolo Aluk community in Tana Toraja in South Sulawesi make religious rituals, such as Rambu Solo’, as an arena of contestation against the domination of the official religions and cultures that existed in South Sulawesi. The ritual of Aluk Todolo community is a kind of Arena to maintain and show identity and religious traditions of the ancestors. In a study conducted in 2004 ago, researcher revealed the facts relating to the community's efforts in Aluk Todolo by displaying their religious ceremonies in the form of renegotiate it with new beliefs or new religion, in this case Christianity. Despite periodic minimization and marginalization against followers of this belief, it acts like Rambu Solo' and Rambu Tuka still often be a very interesting party even though it was done by the Toraja people who have embraced the new religion. This seemed to give the impression that despite the new religion, but some of the teachings of ancestral remains held. Adherents of Faith of the ancestors (alukta) in Tana Toraja or Aluk Todolo community is a typikal community that is still adamant refuse forms of minimization and contextualization by the official religion. Although they are less and less in quantity, but the resistance effort is still underway. Ancestral rituals seems to be a significant form of negotiation in order to maintain the confidence and culture of Aluk Todolo. Because Aluk not be separated by tradition or culture. This is what continues to be done by Tominaa Tato Dena' along with a number of adherents of Aluk Todolo in Tana Toraja.